The appraisal of tropical cyclones in the North Indian Ocean: An overview of different approaches and the involvement of Earth’s components - Tiwari, Gaurav; Kumar, Pankaj; Tiwari, Pooja (Frontiers in Earth Science, 2022)
This study aims to provide a comprehensive and balanced assessment of recent scientific studies on the evolution, temporal variability and prediction of tropical cyclones (TCs), focusing on the North Indian Ocean (NIO). The involvement of earth's components in TC genesis and intensification has been elaborated in a confined way. The advancement of multidisciplinary approaches for comprehending the TCs is highlighted after a brief description of the involvement of oceanic, atmospheric, and land surface processes. Only a few studies illustrate how land surface plays a role in TC intensification; however, the role of latent heat flow, moisture, and convection in cyclogenesis is well documented. Despite two to three decades of advancement and significant development in forecasting techniques and satellite products, the prediction of TC's intensity, dissipation, track, and landfall remains a challenge. The most noticeable improvements in NIO TC's prediction have been achieved in the last couple of decades when concord techniques are utilized, especially the data assimilation methods and dynamical coupled atmosphere-ocean regional models. Through diverse methodologies, algorithms, parameterization, in-situ observational data, data mining, boundary layer, and surface fluxes, significant research has been done to increase the skills of standalone atmospheric models and air-sea coupled models. However, some crucial issues still exist, and it is suggested that they should be addressed in future studies.